GE_GERICHTE PS/34/2017 vom 9. November 2017 - GE Cour de justice (2017)
EXPULSION(DROIT PÉNAL) ; REPORT(DÉPLACEMENT) ; COMPÉTENCE FONCTIONNELLE ; COMPÉTENCE RATIONE MATERIAE ; TRANSMISSION D'UN ACTE PROCÉDURAL | CP.66d; LaCP.40; LaCP.42; REPPL.18